„Ucieczka z systemu”. Edukacja domowa z perspektywy rodziców dzieci szkolnych - Emilia Frasunkiewicz (Problemy Wczesnej Edukacji)
Homeschooling has gained significant interest in the recent years. Despite this, the number of home schooled pupils in Poland does not exceed 0.5% of all students, making homeschooling a niche alternative. This article attempts to discuss the need to revive the awareness around home education, including reasons for choosing this educational path, its advantages, disadvantages, consequences and the level of parental satisfaction. Starting with the critique of the current schooling system as motivation in moving towards educational alternatives, I conclude homeschooling to be an escape from the traditional schooling system. I have analysed data collected from parents of school-aged children in an attempt to recreate their view of contemporary home education. In contrast to existing research, my findings were collected under conditions of remote learning related to the covid19 pandemic. I believe that embedding my research in a quantitative strategy will allow further systematic exploration of this area and consolidation of reliable comprehension of home education in Poland.